Use of nudges for promotion of sustainable energy consumption in households - Dalia Štreimikienė (Contemporary Economics, 2023)
Sustainable energy consumption in household is linked to energy saving and the use of renewable energy sources. These are also the main measures of GHG emission reduction linked to energy consumption. There is a huge GHG emission reduction potential linked to energy consumption in households as climate change mitigation policies and measures aiming at sustainable energy consumption are mainly targeting energy supply sector. Climate change mitigation policies in households linked to promote of energy savings and use of renewable energy sources were not able to overcome behavioural barriers of sustainable energy consumption in households, as they were targeting economic barriers mainly. Therefore, new policies and measures targeting behavioural barriers of sustainable energy consumption inn households are necessary. The paper analyses behavioural barriers of sustainable energy consumption in households and provides analysis of policies and measures set to overcome behavioural barriers of sustainable energy consumption. The analysis of advantages and disadvantages of nudges is provided policy recommendations were developed based on analysis conducted.
Keywords: H30; P18; Q20; Q30; 330; sustainable energy consumption; household; barriers; renewable energy sources; energy savings; nudges